(untitled) (REMUNOM, 2025)
The aging process is characterized by a loss of muscle mass, which consequently reduces strength and resistance, leading to changes in balance and coordination, thus reducing the physical fitness of the elderly. Regular practice of functional training can mitigate this loss of muscle mass, therefore improving the physical fitness of the elderly. Objective: To evaluate the effect of functional training on the general physical fitness index of elderly people. Methods: This is a quasi-experimental research, the sample was selected by convenience in an extension project, totaling 8 participants. The Senior Fitness Test was applied, and the score from each test was added to classify the general physical fitness index. The intervention carried out was functional training, three times a week, lasting 50 minutes. Data collection was carried out in three moments: pre-intervention, two months and twelve months of intervention. Statistical analysis was performed using the JAMOVI program, version (2.3.19). In the present study, descriptive analyzes were carried out using measures of central tendency and dispersion (mean and standard deviation). To check the normality and sphericity of the data, the Shapiro-Wilk and Mauchly’s tests were used, respectively. ANOVA for repeated measures was applied to verify the group interaction effect between moments. Tukey’s Post Hoc was used. An alpha of 0.05 was adopted. The project was approved by the Research Ethics Committee of the Centro Universitário Dr. Leão Sampaio (UNILEÃO), with opinion 5,611,163. Results: The average general physical fitness index was: Pre-intervention: 26 ± 6; two months: 44 ± 12; twelve months: 70 ± 8. Statistical analysis demonstrated a difference over time (p≤0.05). Conclusion: Regular practice of functional training promotes an increase in the general physical fitness of elderly people.